2023
DOI: 10.1007/s00592-023-02137-5
|View full text |Cite
|
Sign up to set email alerts
|

Position paper of the Italian Association of Medical Diabetologists (AMD), Italian Society of Diabetology (SID), and the Italian Study Group of Diabetes in pregnancy: Metformin use in pregnancy

Abstract: Objective This document purpose is to create an evidence-based position statement on the role of metformin therapy in pregnancy complicated by obesity, gestational diabetes (GDM), type 2 diabetes mellitus (T2DM), polycystic ovary syndrome (PCOS) and in women undergoing assisted reproductive technology (ART). Methods A comprehensive review of international diabetes guidelines and a search of medical literature was performed to identify studies presenting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 71 publications
1
11
0
3
Order By: Relevance
“…The package insert now reads: "if clinically indicated, the use of metformin during pregnancy and in the periconceptional period can be considered in addition to or as an alternative to insulin" (agenziafarmaco.gov.it; last accessed: 29 July 2023); thereby leaving an opening for the use of metformin in GDM. After this statement, in July 2023, the Italian Diabetes Society (SID) positively evaluated the possibility of using metformin as a second-line therapy for pregnancies complicated by GDM, even though a careful and precise clinical evaluation of individual cases by an experienced diabetes specialist is advised [133]. The British National Institute for Health and Care Excellence (NICE) is the only national health authority that proposes metformin as a first-line pharmacological therapy for GDM in its guidelines (nice.org.uk; last accessed: 29 July 2023).…”
Section: Why and How The Guidelines On Metformin Use For Gdm Differmentioning
confidence: 99%
See 1 more Smart Citation
“…The package insert now reads: "if clinically indicated, the use of metformin during pregnancy and in the periconceptional period can be considered in addition to or as an alternative to insulin" (agenziafarmaco.gov.it; last accessed: 29 July 2023); thereby leaving an opening for the use of metformin in GDM. After this statement, in July 2023, the Italian Diabetes Society (SID) positively evaluated the possibility of using metformin as a second-line therapy for pregnancies complicated by GDM, even though a careful and precise clinical evaluation of individual cases by an experienced diabetes specialist is advised [133]. The British National Institute for Health and Care Excellence (NICE) is the only national health authority that proposes metformin as a first-line pharmacological therapy for GDM in its guidelines (nice.org.uk; last accessed: 29 July 2023).…”
Section: Why and How The Guidelines On Metformin Use For Gdm Differmentioning
confidence: 99%
“…Conversely, an association was observed between metformin use in non-PCOS mothers and obesity in their children. At present, there is limited clinical evidence to support specific recommendations regarding the use of metformin in pregnant women with PCOS to prevent or treat GDM [ 133 ]. Metformin shows promise in mitigating the risk of late miscarriage and preterm birth in this particular endocrine condition [ 84 ].…”
Section: Why and How The Guidelines On Metformin Use For Gdm Differmentioning
confidence: 99%
“…In the guidelines of the Canadian Diabetes Association, insulin remains the gold standard, while metformin is considered as an alternative approach only in patients with GDM [ 4 ]. Comparably, a board of Italian scientific societies reported that metformin could be used for diabetes in pregnancy as a second-line treatment or in addition to insulin, to reduce its dose, especially in obese women [ 12 ]. According to two expert Greek teams, which were commissioned to construct the national guidelines, no antidiabetic drug, except insulin, should be recommended during pregnancy [ 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the UK’s NICE guidelines recommend metformin as first-line treatment and insulin only under special conditions [ 3 ]. Notably, the Italian guidelines introduce metformin considerations for pregnant women with a body mass index (BMI) over 35 kg/m 2 or women with polycystic ovary syndrome (PCOS), especially when BMI is over 30 kg/m 2 [ 12 ]. However, ADA recommends that metformin should be discontinued by the end of the first trimester, when prescribed pre-pregnancy in women with PCOS to assist with conception [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The apparent volume of distribution is between 63 and 276 L, while the terminal half-life (t 1/2 ) is 4.0–8.7 h [ 97 , 98 ]. Metformin can cross the human placenta and is detectable in small amounts in breast milk with a milk-to-plasma ratio between 0.35 and 0.71 [ 99 ]. Its renal clearance is ~510 ± 120 mL/min, and its half-life is approximately 5 h [ 82 ].…”
Section: Resultsmentioning
confidence: 99%